The quality of the teaching process, a system for its management in the bachelor's Degree in Economics at the University of Pinar del Río, Cuba (Revista Electrónica Calidad en la Educación Superior, 2019)
The search of the continuous improvement of the quality of the university processes, constitutes a priority of the management of the institutions of superior education. Requiring greater relevance in the processes of development of societies, higher education requires that its substantive processes achieve results that can contribute pertinently to the solution of the problems of diverse nature present in their contexts. In this effort, the proposal of a quality management system for the teaching process is conceived, of the Bachelor's Degree in Economics from the University of Pinar del Río, Cuba; that tribute to the strengthening of the training of professionals of this branch in this province of the west of the country.
Keywords: system; management; quality; teaching process; system